Exploration of beta-arrestin isoform signaling pathways in delta opioid receptor agonist-induced convulsions - Blaine, Arryn T.; Miao, Yiming; Yuan, Jinling; Palant, Sophia; Liu, Rebecca J.; Zhang, Zhong-Yin; van Rijn, Richard. M. (Frontiers in Pharmacology, 2022)
The δ-opioid receptor (δOR) has been considered as a therapeutic target in multiple neurological and neuropsychiatric disorders particularly as δOR agonists are deemed safer alternatives relative to the more abuse-liable µ-opioid receptor drugs. Clinical development of δOR agonists, however, has been challenging in part due to the seizure-inducing effects of certain δOR agonists. Especially agonists that resemble the δOR-selective agonist SNC80 have well-established convulsive activity. Close inspection suggests that many of those seizurogenic δOR agonists efficaciously recruit β-arrestin, yet surprisingly, SNC80 displays enhanced seizure activity in β-arrestin 1 knockout mice. This finding led us to hypothesize that perhaps β-arrestin 1 is protective against, whereas β-arrestin 2 is detrimental for δOR-agonist-induced seizures. To investigate our hypothesis, we characterized three different δOR agonists (SNC80, ADL5859, ARM390) in cellular assays and in vivo in wild-type and β-arrestin 1 and β-arrestin 2 knockout mice for seizure activity. We also investigated downstream kinases associated with β-arrestin-dependent signal transduction. We discovered that δOR agonist-induced seizure activity strongly and positively correlates with β-arrestin 2 efficacy for the agonist, but that indirect inhibition of ERK activation using the MEK inhibitor SL327 did not inhibit seizure potency and duration. Inhibition of the PI3K/AKT/mTOR signaling with honokiol but not PQR530, attenuated SNC80 seizure duration in β-arrestin 1 knockout, but honokiol did not reduce SNC80-induced seizures in wild-type mice. Ultimately, our results indicate that β-arrestin 2 is correlated with δOR agonist-induced seizure intensity, but that global β-arrestin 1 knockout mice are a poor model system to investigate their mechanism of action.